The adverse effects of 17β-estradiol immersion during gonadal differentiation on ovarian development of female Takifugu rubripes - Hu, Peng; Liu, Shufang; Liu, Xinfu; Liu, Haijin; Liu, Shengcong; Zhuang, Zhimeng (Frontiers in Marine Science, 2023)
Estrogen exposure during early-life stages has been found to delay ovarian development in female fish, even after a long-term depuration period. However, the mechanisms underlying the disordered ovarian development remain unclear. In this study, the larvae of tiger puffer Takifugu rubripes were exposed to 0 (control) and 10 μg/L 17β-estradiol (E2) from 20 to 90 days post-hatch (dph) and maintained in clear seawater until 180 dph. Genetic females collected at 90 and 180 dph were identified by analyzing a sex-associated SNP. Then, the ovarian structure, gonadosomatic index (GSI), the maximum follicle area and the mRNA levels of genes involving in cell cycle (ckd2, ckd4, cdk6, ccna2, ccnd2, cdkn1b and cdkn2c), meiosis initiation (sycp3, rec8, spo11, and dmc1), follicle formatiaon (bmp2, hnrnpk, hmp15, gdf9, nobox and figla) and apoptosis (bax and bcl-2) were analyzed between control and E2-exposed females. The results show that, no structure difference in ovaries was observed between control and E2-treated females at 90 dph, but the primary growth follicles in E2-treated females were observed to be fewer in number than control at 180 dph. Both ovarian weight and GSI of E2-treated females were significant lower than the control at 90 and 180 dph, while there was no significant different in the maximum follicle area between control and E2-treated females at neither 90 or 180 dph. Additionally, the E2 exposure suppressed the expression of sycp3, rec8, spo11, dmc1, bmp2, hnrnpk and bcl-2 at 90 dph, but the mRNA levels of those genes in E2-treated females showed no significant different with the control at 180 dph. The reduced mRNA levels of sycp3, rec8, spo11 and dmc1 might result in disrupted meiosis, and suppression the expression of bmp2 and hnrnpk affected follicle formation. Then, abnormal meiosis initiation and follicle formation might further promote apoptosis as indicated by the decrease in mRNA levels of bcl-2, which ultimately contributed to less number of follicles and low GSI value in E2-treated females.